Anomalous microwave response of YBa2Cu3O7-δ granular thin films under magnetic fields. - Ke-Xi Xu (IEEE Transactions on applied superconductivity)
The microwave response of YBa2Cu3O7-δ (YBCO) granular films has been studied at a microwave frequency of 30.5 GHz. In absence of a magnetic field, the dependencies of a normal microwave response on the bias current was observed at a temperature close to Tc. When a magnetic field ranging from 5.0 to 33.0 mT is applied, the responses broaden and shift toward a lower temperature. In the superconducting state, the responses were found to be highly dependent on the magnetic field. For a current of 5.0 mA and a magnetic field above 17.0 mT, the responses increased and did not vanish, even at a very low temperature, which is believed to be correlative with the anisotropic character of the structure